Risk factors for postoperative pulmonary complications following coronary artery bypass grafting in elderly patients: a retrospective study - Guang Feng; Yitong Jia; Guanxu Zhao; Ying Zhang; Tianlong Wang (Journal of Cardiothoracic Surgery)
Abstract Background Postoperative pulmonary complications (PPCs) significantly impact the prognosis of elderly patients undergoing coronary artery bypass grafting (CABG), yet the risk factors for PPCs in CABG remain uncertain. The objective of this study is to identify risk factors for PPCs in elderly patients undergoing CABG. Methods This study retrospectively analyzed 305 elderly patients who underwent CABG at Xuanwu Hospital, from January 2019 to December 2023. The variables analyzed included patient demographics, comorbidities, anesthesia factors, surgical factors and perioperative laboratory tests. Based on the occurrence of PPCs, patients were divided into the PPC group and the none-PPC group. Univariate analysis and multivariate logistic regression analysis were employed to determine the independent risk factors of PPCs in elderly patients undergoing CABG. Results Of the 305 patients, 148 developed PPCs, resulting in an incidence rate of 48.5%. Compared to the none-PPCs group, patients in the PPCs group had significantly longer postoperative lengths of stay and higher perioperative mortality rates. The results indicated that NYHA classification ≥ III (P = 0.024, OR: 1.791, 95%CI: 1.080 ~ 2.972), preoperative P/F ratio (PaO2/FiO2) < 350 mmHg (P = 0.002, OR: 2.363, 95%CI: 1.371 ~ 4.073) and postoperative albumin level (P = 0.020, OR: 0.946, 95%CI: 0.903 ~ 0.991) were independent risk factors for PPCs in elderly patients undergoing CABG. Conclusion This study identified NYHA classification ≥ III, preoperative P/F ratio < 350 mmHg and postoperative albumin levels as independent predictors of PPCs in elderly patients undergoing CABG. Further study is needed to validate these findings and explore potential interventions to mitigate the risk of PPCs in elderly CABG patients.